THE RELATIONSHIP OF INTERNET ADDICTION WITH SOCIAL INTERACTION IN ADOLESCENTS - ESTER MEINELSA MANURUNG; IDA LISTIANA; MIFTAH AFIFAH ZAHRANI; FENITA PURNAMA SARI INDAH; LUKMAN HANDOYO (NURSING ANALYSIS: Journal of Nursing Research, 2022)
ABSTRACTThe results of We Are Social and Hootsuite (2020) Indonesia is ranked third with the largest internet access population growth of 17% in the last year or 25.3 million new internet accesses. Indonesia is also ranked eighth in the world with the longest access time where the first rank is the Philippines for 9 hours 45 minutes using internet-facilitated media, while the world average is "only" 6 hours 43 minutes. Objective: The purpose of this study was to determine the relationship between internet addiction and social interaction in adolescents at SMK Putra Pertiwi Pondok Cabe. Methods: This study uses quantitative methods and uses an analytical design with a Cross Sectional approach. Sampling was carried out using the Probability Sampling method with the Simple Random Sampling technique for students in class X and XI at SMK Putra Pertiwi Pondok Cabe (n=95). The data were then analyzed using the Chi-Square test (p-value < 0.05). Results: The results of this study indicate that respondents who have severe internet addiction are 53.7%, interactions with parents are not good as much as 68.4%, interactions with peers are not good as many as 80%, interactions with the school environment are not good as much as 77.9%, and interaction with the community that is not good as much as 66.3%. Conclusion: This study shows that there is a relationship between internet addiction and social interaction with parents (P-value = 0.002), peers (P-value = 0.000), school environment (P-value = 0.003), and community environment (P-value = 0.003). value = 0.023). Suggestion: Teenagers are expected to be wiser in using the internet and not be ignorant of their surrounding. Keywords: adolescence, internet addiction, social interaction HUBUNGAN KECANDUAN INTERNET DENGAN INTERAKSI SOSIAL PADA REMAJA ABSTRAKHasil We Are Social and Hootsuite (2020) Indonesia ada di peringkat ke tiga dengan pertumbuhan populasi pengaksesan internet terbesar sebesar 17% dalam satu tahun terakhir atau 25,3 juta pengaksesan internet baru. Indonesia juga masuk peringkat ke delapan di Dunia dengan waktu akses terlama dimana peringkat pertama adalah Filipina selama 9 jam 45 menit dengan menggunakan media yang difasilitasi internet, sementara rata-rata dunia “hanya” 6 jam 43 menit. Tujuan: Tujuan penelitian ini adalah untuk mengetahui hubungan kecanduan internet dengan interaksi sosial pada remaja di SMK Putra Pertiwi Pondok Cabe. Metode: Penelitian ini menggunakan metode kuantitatif dan menggunakan desain analitik dengan pendekatan Cross Sectional. Pengambilan sampel dilakukan dengan menggunakan metode Probability Sampling dengan teknik Simple Random Sampling pada siswa-siswi kelas X dan XI di SMK Putra Pertiwi Pondok Cabe (n=95). Data tersebut kemudian dianalisis menggunakan uji Chi-Square (p-value α < 0,05). Hasil: Hasil penelitian ini menunjukkan bahwa responden yang memiliki kecanduan internet berat sebanyak 53,7%, interaksi dengan orang tua yang kurang baik sebanyak 68,4%, interaksi dengan teman sebaya yang kurang baik sebanyak 80%, interaksi dengan lngkungan sekolah yang kurang baik sebanyak 77,9%, dan interaksi dengan lingkungan masyarakat yang kurang baik sebanyak 66,3%. Kesimpulan: Penelitian ini menunjukkan bahwa ada hubungan antara kecanduan internet dengan interaksi sosial dengan orangtua (P-value = 0,002), teman sebaya (P-value = 0,000), lingkungan sekolah (P-value = 0,003), dan lingkungan masyarakat (P-value = 0,023). Saran: Remaja diharapkan dapat lebih bijak lagi dalam menggunakan internet dan tidak abai dengan keadaan sekitar. Kata kunci: interaksi sosial, kecanduan internet, remaja